Improved root zone temperature buffer capacity enhancing sweet pepper yield via soil-ridged substrate-embedded cultivation in solar greenhouse - Fu, Guohai; Li, Zonggeng; Liu, Wenke; Yang, Qichang (International Journal of Agricultural and Biological Engineering, 2018)
A novel soilless cultivation method, called as soil-ridged substrate-embedded cultivation (SSC) was invented, and an experiment was designed to investigate root zone temperature and production efficiency of sweet pepper cultivated by two SSC patterns, i.e., SSC-P (polyethylene groove inserted) and SSC-W (wire-mesh groove inserted), and also other two cultivation methods, i.e., soil ridge (SR) and naked polyethylene groove (PG). Results showed that PG, SSC-P and SSC-W increased the average minimal root zone temperature by 1.01°C, 0.75°C, and 1.16°C compared to SR (16.33°C) during March 16-20, 2015. During June 1-5, SSC-P and SSC-W decreased the average maximal root zone temperature by 1.28°C and 1.29°C compared to SR (34.99°C), while PG increased it by 1.44°C. PG, SSC-P, and SSC-W decreased the differences of average daytime and night time temperatures by 1.34°C, 2.13°C, and 2.88°C compared to SR (4.56°C) during early stage. However, SSC-P and SSC-W decreased temperature differences of average daytime and night time by 0.9°C and 1.07°C compared to SR (0.95°C) during later stage, but PG improved by 2.85°C. Temperature difference of daytime and night time of SSC-W was minimal, and the temperature difference between the diurnal highest and the lowest temperature of SSC-W was also minimal. The buffer capacity of SSC-W was slightly better than that of SSC-P. SSC-W significantly improved the growth of sweet pepper compared to SR. Similarly, fruit yield per square meter of sweet pepper cultivated on SSC-P and SSC-W improved by 21.24% and 50.33%, respectively compared to SR (3.06 kg/m2), while PG lowered the yield by 13.72%. SSC-W was a better SSC pattern compared with SSC-P in terms of production efficiency. Keywords: soil cultivation, SSC, substrate cultivation, solar greenhouse, diurnal temperature difference, root zone temperature DOI: 10.25165/j.ijabe.20181102.2679 Citation: Fu G H, Li Z G, Liu W K, Yang Q C. Improved root zone temperature buffer capacity enhancing sweet pepper yield via soil-ridged substrate-embedded cultivation in solar greenhouse. Int J Agric & Biol Eng, 2018; 11(2): 41–47.